2023
DOI: 10.2478/bjreecm-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Possible Solutions of Post-Disaster Housing Reconstruction Projects in India

Abstract: Natural disasters occur often around the globe and result in significant loss of life and property. Over the last two decades, there has been a remarkable rise in extreme weather events that have the potential to wreak devastation on the planet. Frequently, disaster-affected regions needed to enhance their capacity for rebuilding, requiring more experienced and competent personnel to oversee the projects. Post-disaster reconstruction (PDR) is a complicated and difficult procedure requiring a variety of distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…This study identified 24 resilience factors, divided into 5 criteria groups, in an attempt to develop a new conceptual framework to guide developers and practitioners in improving resilience in postdisaster reconstruction projects. In [15], damaged city areas demonstrated the need to strengthen their rebuilding capacity, requiring more experienced and efficient workers to supervise projects. This study attempted to analyze the problems associated with post-disaster housing reconstruction projects in India and provide potential solutions, concluding that institutional procedures, reconstruction techniques, project implementation, and stakeholder management contribute to effective implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study identified 24 resilience factors, divided into 5 criteria groups, in an attempt to develop a new conceptual framework to guide developers and practitioners in improving resilience in postdisaster reconstruction projects. In [15], damaged city areas demonstrated the need to strengthen their rebuilding capacity, requiring more experienced and efficient workers to supervise projects. This study attempted to analyze the problems associated with post-disaster housing reconstruction projects in India and provide potential solutions, concluding that institutional procedures, reconstruction techniques, project implementation, and stakeholder management contribute to effective implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Significant hurdles to the redevelopment of unoccupied property are monetary [20]. Most communities lack the appropriate economic incentives to encourage the maintenance and improvement of unoccupied land and abandoned structures, heritage sites [12; 13], and historical buildings [21].…”
Section: Literature Reviewmentioning
confidence: 99%